6x+4=-4x-26

Simple and best practice solution for 6x+4=-4x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4=-4x-26 equation:


Simplifying
6x + 4 = -4x + -26

Reorder the terms:
4 + 6x = -4x + -26

Reorder the terms:
4 + 6x = -26 + -4x

Solving
4 + 6x = -26 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
4 + 6x + 4x = -26 + -4x + 4x

Combine like terms: 6x + 4x = 10x
4 + 10x = -26 + -4x + 4x

Combine like terms: -4x + 4x = 0
4 + 10x = -26 + 0
4 + 10x = -26

Add '-4' to each side of the equation.
4 + -4 + 10x = -26 + -4

Combine like terms: 4 + -4 = 0
0 + 10x = -26 + -4
10x = -26 + -4

Combine like terms: -26 + -4 = -30
10x = -30

Divide each side by '10'.
x = -3

Simplifying
x = -3

See similar equations:

| 1/2y-3=13 | | 85.00+7.50d=130.00 | | D/-2=-48 | | 7*5=59-j | | 44+n=5*9 | | -3=x/-21 | | 5y-10=3y+26 | | 85.00+7.50d=30.00 | | (-78c)-(-75c)+(-68c)-(-54c)+12c-(-67)=(-28) | | 6+35=m-8 | | -24=h/-3 | | 3x-1-5x+5=105 | | 10z-5z-2z-3=45 | | 3x-1+5x+5=105 | | 3=f/-15 | | 92t-38t+(-79t)-(-30t)=(-75) | | 66-w=16+1 | | 3x-1-5x+5=180 | | 7c-6=29 | | 120+40r=800 | | (-25d)-(-12d)+(-37)=54 | | 5y+6=6y-7 | | K/-4=-11 | | 7c-4=29 | | (-70x)+52x+36x-(-83x)-95x=(-84) | | 4*6=n*2 | | T/-8=12 | | z+47=33+18 | | 21g+19g+2g-25g-6g=99 | | 5b-4=26 | | 34s-4s-24s-3s-3=87 | | (-37h)-(-46h)-28=71 |

Equations solver categories